Development and validation of novel stability indicating RP HPLC Method for quantitative Estimation of Empagliflozin in Tablets (Indian Journal of Pharmacy & Drug Studies, 2023)
The current study was conducted to develop and validate a novel method for the qualitative and quantitative determination of Empagliflozin in bulk granules and tablets. This method was successively applied to the analysis of the approved dosage form of Empagliflozin available in the market with the brand name of Jardiance tablets. The developed method was found to be precise, economic, and rapid with a run time of 20 minutes. The Empagliflozin peak was eluted at 5.0 minutes. This elution was done on the C18 column (150 X 4.6mm) having a 5μm particle size using an isocratic mobile phase, a mixture of phosphate buffer pH 3.0 and methanol in the ratio of 70:30 at a flow rate of 1.0ml/min with PDA detector (maximum wavelength of 224nm) and column temperature 30°C. The method was found to be linear with LOD and LOQ, 0.068 μg and 0.35 μg, respectively. The correlation coefficient R2 calculated was 0.996. Precision and accuracy of the method evaluated by interday, intraday, and recovery study was found to be within limits. The forced degradation study proved the stability of the method. Objectives: This research article is aimed at developing a new method for developing and validating a novel method for the qualitative and quantitative determination of Empagliflozin in bulk granules and tablets.  Methods: To conduct this research, all the validation parameters were employed according to International Council for Harmonization (ICH) guidelines and all the validation parameters e.g., Accuracy, specificity, linearity, LOD, LOQ, robustness, and degradation studies were performed. Results: Results of the proposed technique were found to be trustworthy, accurate, suitable, and robust for everyday application. Conclusion: Conclusively the results of the study indicated that the current method is simple, precise, accurate, stable, and economic, and thus can be used for routine quality control testing of Empagliflozin.